Impacted Metallic Spring Requiring Cervical Esophagotomy: A Case Report and Review of the Literature on Foreign Body Removal - Patrick Stoner; Eric Hilgenfeldt; Alexander Schlachterman (Case Reports in Gastrointestinal Medicine)
Foreign body ingestion is a commonly encountered problem and can cause significant morbidity and mortality. When removal of a foreign body from the upper gastrointestinal tract is indicated, endoscopy is the modality of choice and has a high reported success rate. However, in less than 1% of cases, endoscopic removal of a foreign body is unsuccessful and surgical intervention is necessary. We report a unique case of a large, sharp metallic spring swallowed by an incarcerated patient which subsequently became lodged in his upper thoracic esophagus. This spring was unable to be removed endoscopically due to risk of perforation and cervical esophagotomy was needed for its successful removal, illustrating the limitations of endoscopic techniques in removal of foreign bodies and the role surgical intervention has in these rare instances.